Liu Yuzhen Is Dead. (2nd July 2020) - Zhang, Ning; Field, Jesse
Abstract : "Liu Yuzhen Is Dead" is one of the anecdotes from Luo Town collected in Zhang Ning's 2019 work Hallucinations . Applying a style spare in description but rich and colorful in dialogue, Zhang deftly sketches characters in small-town China. Anyone who has worked as a medical professional, or has one in the family, will relate to tales about the patients they have seen. See the full collection for more drama involving Liu Yuzhen and her blustery husband, Luo Changsheng. Originally published in Renmin wenxue ( People's Literature ) issue 1, 2019.